Elementary Structures Reconsidered : Levi-Strauss on Kinship. - Korn, Francis (Taylor and Francis, 2013)
Constituting a measured but devastating critique of Lévi-Strauss's work on kinship systems, this book deals with prescriptive forms of social classification and had far-reaching implications for anthropological theory when it was originally published. Originally published in 1973.